Effect of COVID-19 on rural community enterprises: Case of community forest enterprises in Cameroon - Piabuo, S.M.; Tsafac, S.; Minang, Peter A.; Foundjem-Tita, D.; Guimke, G.; Duguma, L.A. (World Agroforestry Centre, 2021)
The COVID-19 outbreak has been a big shock to the entire world. The global economic slowdown and loss of human life have been highlighted as immediate impacts of the virus. Rural forest communities and their enterprises have also been affected in different ways. This study seeks to extend the current understanding of the impacts of COVID-19 by evaluating how it has affected rural community forest enterprises (CFEs) in Cameroon. A sample of 13 CFEs makes up the study. Focus-group discussions with a well-structured interview guide were used for data collection. Descriptive statistics were used for analysis. The results reveal that CFEs dealing in perishable products suffered more from the effects of restrictive government measures to contain the virus than enterprises dealing in non-perishable products. Transport costs for most activities doubled for all enterprises; labour supply was reduced by 72.5% for CFEs dealing in perishable products and 50% for enterprises dealing with non-perishable products. The commercialization of CFEs’ products was also adversely affected: market prospects reduced by 100%; sale prices of products reduced by 57% for perishable products and by 60% for non-perishable products; and global commercialization costs increased by 100%, for all CFEs. With the virus outbreak, CFEs also were challenged engaging with their partners, especially donors, technical support organizations and the private sector. The study recommends exploiting value-addition options through the processing of perishable products to improve enterprise resilience to such exogenous shocks.